2011
DOI: 10.1021/jm200609t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Brain-Penetrant S1P3-Sparing Direct Agonist of the S1P1 and S1P5 Receptors Efficacious at Low Oral Dose

Abstract: 2-Amino-2-(4-octylphenethyl)propane-1,3-diol 1 (fingolimod, FTY720) has been recently marketed in the United States for the treatment of patients with remitting relapsing multiple sclerosis (RRMS). Its efficacy has been primarily linked to the agonism on T cells of S1P(1), one of the five sphingosine 1-phosphate (S1P) G-protein-coupled receptors, while its cardiovascular side effects have been associated with activity at S1P(3). Emerging data suggest that the ability of this molecule to cross the blood-brain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…These data suggest that S1P 1 can also accommodate mildly bent shapes, but that S1P 2 and S1P 4 prefer more linear ligand geometries. The ability of S1P 3 to recognize both bent and linear shapes demonstrates why achieving S1P 1 -selective agonists that lack the bradycardia side effect mediated by S1P 3 action has been achieved by large jumps in structural space from the flexible phospholipid agonist analogs of S1P [11,13,1719,21,22,25,36,41,42]. …”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that S1P 1 can also accommodate mildly bent shapes, but that S1P 2 and S1P 4 prefer more linear ligand geometries. The ability of S1P 3 to recognize both bent and linear shapes demonstrates why achieving S1P 1 -selective agonists that lack the bradycardia side effect mediated by S1P 3 action has been achieved by large jumps in structural space from the flexible phospholipid agonist analogs of S1P [11,13,1719,21,22,25,36,41,42]. …”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, teratogenicity has been observed in rodents, and the long half-life in humans (8 days) requires contraception for two months after stopping treatment. 18 A further challenge is identifying therapeutics with appreciable central exposure as this is believed to be necessary for success in treating MS. 19 Lastly, new agents with reduced hepatotoxicity in humans would be highly beneficial. Herein we report the discovery of APD334 (4, Figure 1), a centrally available, selective, functional antagonist of the S1P 1 receptor currently in development for the treatment of autoimmune disease.…”
mentioning
confidence: 99%
“… 19 Studies have demonstrated that BAF312 (1 h at 1 μM) promotes significant internalization of the 91% of S1P1 receptors and downregulates S1PR1 expression. 20 In addition, a previous study found that fingolimod (FTY720), the first-generation S1PR modulator, can resensitize chemoresistant ovarian cancer cells to cisplatin by downregulating S1PR1. 21 The efficacy of BAF312 in reversing platinum-resistant ovarian cancer has not yet been evaluated in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%